P60 "It's like the service that was never there": a qualitative longitudinal study of lay health trainer services in the North East of England. (16th November 2010) - Visram, S; Clarke, C; White, M
Abstract : Background: Despite considerable improvements in the overall health of the UK population, the gap between the richest and poorest groups in society continues to widen. Health trainers are a new workforce introduced in the 2004 "Choosing Health" White Paper to address these inequalities by targeting individuals from the poorest groups and supporting them to make healthy lifestyle choices. The largely grass-roots development of health trainers has resulted in a diversity of local service models that lack sound theoretical or empirical basis. However, the role provides an opportunity to enhance our understanding of the needs of typically "hard-to-reach" communities and develop tailored behaviour change interventions. Objectives: To conduct an in-depth exploratory study of the ways in which contrasting health trainer models influence behaviour change. Design: Qualitative longitudinal study, involving serial interviews conducted over a 12-month period. The interviews have been audio-recorded, transcribed verbatim and analysed using the constant comparative method associated with grounded theory. Setting and Participants: 26 clients, 13 health trainers and 5 managers theoretically sampled from 3 local health trainer services in the North East of England. Results: The health trainer services are characterised by diversity in terms of the main target groups, modes of client engagement and degree of emphasis on individual behaviour change. This has implications for the extent to which they are integrated (or not) into local public health systems, and also for the experiences of staff and service users. An emerging theme is the perception that these services are more flexible and holistic than similar lifestyle interventions, and that they address multiple priorities for clients. The importance of delivering interventions in appropriate settings was emphasised, particularly where clients have limited or negative experience of accessing other forms of support. The fact that health trainers tend to be members of the local community was often perceived to act as a facilitator of clients' ongoing engagement with the service. Conclusions: These preliminary findings highlight the potential role for health trainers in engaging with individuals from disadvantaged areas and attempting to facilitate their access into the health care system. Health Trainers are being embedded as an integral part of regional and local work on tackling health inequalities, as well as addressing a cross-government agenda. The findings of this study will be used to inform the development and evaluation of the role, as well as generating new evidence to assist practitioners in overcoming the barriers to successfully working with local communities.